Antioxidant potential and biochemical evaluation of metabolites from the marine bacteria Virgibacillus sp. associated with the sponge Callyspongia diffusa - Arunachalam, Kalirajan; Appadorai, Ranjitsingh Amirtham Jacob (Free Radicals and Antioxidants)
Objective: In this present research, the antioxidant activity of the metabolites produced by the marine bacteria Virgibacillus sp. associated with the sponge Callyspongia diffusa was evaluated and the crude metabolites was also tested to find out the chemical compounds. Methods: In view of testing the antioxidant activity, DPPH radical scavenging activity, Hydroxyl radical scavenging activity, Superoxide radical scavenging activity, Nitric oxide radical scavenging activity,, Metal chelating, Ferric reducing antioxidant power were carried out invitro. Results: The DPPH radical scavenging activity was 46.56% at 2000 mg/ml and the IC50 value was 857.49 mg/ ml, The hydroxyl radical scavenging activity was found significant (60.77% at 2 mg/ml) and the IC50 value was found 471.07 mg/ml. Superoxide radical scavenging activity was 25.58% at 2000 mg/ml and the IC50 was 1353.28 mg/ml, for nitric oxide, the radical scavenging activity was 25.58% at 2000 mg/ml concen- tration and in the due course the IC50 value was 1353.28 mg/ml. The results of the chemical analysis showed the presence of chemical components such as alkaloids, terpenoids, reducing sugars and anthraquinones. Conclusion: This research revealed the potential of marine sponge-associated bacterial bioactive com- pounds in scavenging the free radicals invitro. Separation of individual compounds from the crude metabolites of Virgibacillus sp. associated with the marine sponge C. diffusa will be resulted in the development of a novel antioxidant molecule.
Keywords: Antioxidants; Callyspongia diffusa; Marine drug; Virgibacillus sp